The Rights to Health Of Worker From the Perspective of Indoor Air Quality - Amriyati Amriyati (Green Publisher Indonesia, 2022)
Indoor air quality really effects persons’ health, including workers whose time mostly spent at work. Persons’ conduct may create pollutant which effect indoor air quality. Unhealthy indoor air has caused more than four million people dead from pneumonia, stroke, systemic heart decease, obstructive lung decease and cancer. Persons’ conduct must be regulated by law to ensure one’s rights and obligation do not violate others. This research was focused on how the rights to health of the workers from the perspective of indoor air quality was protected by law and what obligations were generated from the rights towards workers, employers and the state. This research was an analytical descriptive doctrinal one using library research to gain secondary data from related legislation and regulation as well as expert commentaries in textbooks and scientific journal articles. To ensure indoor air quality for workers, the workers themselves and the employers must be equipped with the knowledge and comprehension of the rights they possess and the obligation attached with the rights to implement the law on how they have to conduct to ensure the participation in the availability of healthy indoor air quality. Workers and employers shall not act nor omit which might resulted in unhealthy indoor air at work room through ensuring fresh air circulation, avoiding smoke and other polluting substances use in indoor rooms.